Chemical constituents from Ficus deltoidea var. kunstleri corner and its antidiabetic property - Nor Afifah Md Jamal (N/A, 2017)
Chemical constituents from Ficus deltoidea var. kunstleri corner and its antidiabetic property by Nor Afifah Md Jamal